2018
DOI: 10.1111/eci.12897
|View full text |Cite
|
Sign up to set email alerts
|

A Western dietary pattern is associated with elevated level of high sensitive C‐reactive protein among adolescent girls

Abstract: Our results indicate that there is a significant positive association between more adherence to Western dietary pattern and higher serum levels of hs-CRP among Iranian adolescent girls. Further studies, particularly longitudinal intervention studies may be required to clarify these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
(87 reference statements)
4
20
0
2
Order By: Relevance
“…Gianfredi et al have shown that diet may have a substantial impact on several sleep disturbances, including insomnia [8]. Dietary patterns can be extracted using posteriori or priori methods [911]. The Dietary Approach to Stop Hypertension (DASH)- style diet which is characterized by a high consumption of whole grains, vegetables, fruits, low-fat dairy, nuts and legumes, and restricted amounts of red or processed meat, sweets, and sugar-sweetened beverages, can be identified as a priori dietary pattern [12].…”
Section: Introductionmentioning
confidence: 99%
“…Gianfredi et al have shown that diet may have a substantial impact on several sleep disturbances, including insomnia [8]. Dietary patterns can be extracted using posteriori or priori methods [911]. The Dietary Approach to Stop Hypertension (DASH)- style diet which is characterized by a high consumption of whole grains, vegetables, fruits, low-fat dairy, nuts and legumes, and restricted amounts of red or processed meat, sweets, and sugar-sweetened beverages, can be identified as a priori dietary pattern [12].…”
Section: Introductionmentioning
confidence: 99%
“…The first study was longitudinal and found an association between WDP adherence at 14-years and higher levels of hs-CRP at 17-years both in healthy males and females ( Oddy et al., 2018 ). The remaining two observational studies found an association between WDP adherence, and higher levels of CRP and IL-6 in this case in female cohorts of healthy participants ( Del Mar Bibiloni et al., 2013 ; Khayyatzadeh et al., 2018 ). Similarly, across the six observational studies ( Lazarou et al., 2010 ; Sen et al., 2018 ; Almeida-de-Souza et al., 2018 ; Coheley et al., 2019 ; Seremet Kurklu et al., 2020 ; Shivappa et al., 2017 ) that examined the Dietary Inflammatory Index (DII), a tool that assesses the inflammatory potential of a diet ( Suhett et al., 2020 ), diets with high inflammatory potential (a higher score in the DII), inducing a higher inflammatory response were positively associated with pro-inflammatory biomarkers in males and females.…”
Section: Dietary Intake and Inflammationmentioning
confidence: 62%
“…In contrast to healthful dietary patterns, three studies examined the Western dietary pattern ( Del Mar Bibiloni et al., 2013 ; Oddy et al., 2018 ; Khayyatzadeh et al., 2018 ). This pattern is characterised by high amounts of refined grains, red meat, high-fat dairy, ultra-processed food intake and trans fatty acids while being low in omega-3 PUFAs ( Li et al., 2020 ; Okręglicka, 2015 ).…”
Section: Dietary Intake and Inflammationmentioning
confidence: 99%
“…Alongside cardiovascular complications, obesity and type 2 diabetes are important risk factors in the pathogenesis of cognitive dysfunction [11][12][13]. On the cellular level, a Western diet is associated with reduced expression of brain-derived neurotrophic factors, elevated levels of oxidative stress, and pro-inflammatory processes in neurons, and affects the whole-body immune response [14].…”
Section: Introductionmentioning
confidence: 99%